Effects of Dl-3-n-butylphthalide on neurological function, hemodynamics and Hcy concentration in cerebral hemorrhage: a systematic review and meta-analysis - Ma, Yingqi; Guo, Chenchen; Wang, Yiguo; Liu, Xinxin (Frontiers in Pharmacology, 2024)
Background: Dl-3-n-Butylphthalide (NBP) has emerged as a potential therapeutic agent for cerebral hemorrhage, despite not being included in current guideline recommendations. Investigating the underlying physiological and pathological mechanisms of Dl-3-n-Butylphthalide in cerebral hemorrhage treatment remains a critical area of research. Objective: This review aims to evaluate the efficacy of Dl-3-n-Butylphthalide in cerebral hemorrhage treatment and elucidate its potential biological mechanisms, thereby providing evidence to support treatment optimization. Methods: A comprehensive search of 7 electronic databases(PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, VIP, and Wanfang Database ) was conducted for studies published up to September 2023. Screening and data extraction were performed by a team of researchers. The Cochrane collaboration tool was utilized for risk bias assessment, and Revman 5.3 along with Stata 17.0 were employed for statistical analysis. Outcomes: We searched 254 literatures, and 19 were included in this meta-analysis. The results showed that Dl-3-n-Butylphthalide improved the clinical efficacy rate (RR = 1.25, 95% CI 1.19~1.31; p= 0.00), quality of life (MD = 13.93, 95% CI: 11.88~15.98; p= 0.000), increased cerebral blood flow and velocity, reduced cerebral edema volume, Hcy concentration and SP, and did not have obvious adverse reactions (RR = 0.68, 95% CI: 0.39~1.18; p= 0.10). Conclusions: This meta-analysis is the first to demonstrate the potential of Dl-3-n-Butylphthalide in treating cerebral hemorrhage. It suggests that Dl-3-n-Butylphthalide may alleviate clinical symptoms by modulating neurological function and improving hemodynamics. Our findings provide robust evidence for incorporating Dl-3-n-Butylphthalide into cerebral hemorrhage treatment strategies, potentially guiding future clinical practice and research.